ANALISIS YURIDIS JAMINAN SOSIAL KESEHATAN DALAM UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - Sutrisno, Hafiz; Maimory, Aminoel Akbar Novi (Pahlawan Tuanku Tambusai University, 2022)
Health services must be understood not only as services for people who are sick, but also guaranteeing public health as a whole. The right to health is one of the rights regulated in the constitution. The fact that so far the public's health status is still low, especially for the poor, this can be illustrated by the fact that the maternal mortality rate and infant mortality rate for the poor are three times higher than for non-poor people. Likewise what happens to workers or workers who are working in a company where usually their rights as workers are not fully owned. As a worker, workers have the right to be guaranteed their health and future while working and after retirement. The formulation of the problem in this study is how to regulate health insurance based on Law Number 24 of 2011 concerning Social Security Administering Bodies and how BPJS Health forms social protection. This research is normative juridical law research, because it wants to find legal rules, legal principles, and legal doctrines to answer the legal issues at hand. The government, which is responsible for guaranteeing the health of its citizens, forms the Social Security Administering Body or abbreviated BPJS, which was born based on Law Number 24 of 2011. Keywords: Social Security, BPJS